On Becoming a Group Member : Personal Growth and Effectiveness in Group Counseling. - Shakoor, Muhyiddin (Taylor & Francis, 2010)
This book provides an introduction to the general landscape of group counseling by way of the idea that learning to be an effective group member is essential to becoming a group leader.€Interactive scenarios place the reader right into the group, providing insights into the challenges and opportunities of participation.€Each chapter explores a different stage of group work and concludes with useful suggestions and tips for having a successful experience.€Throughout the book, an emphasis is placed on member development and personal growth being achieved through self-awareness, in.